Neuroprotective and antioxidant activities of different polarity parts of the extracts of the Ginkgo biloba leaf and Zingiber officinale rhizome from Yongzhou - Zuoying Huang; Zuoying Huang; Zuoying Huang; Tingting Yuan; Tingting Yuan; Tingting Yuan; Jiayi Chen; Jiayi Chen; Jiayi Chen; Mihan Jiang; Mihan Jiang; Mihan Jiang; et al. (Frontiers in Chemistry, 2022)
In order to make better use of the two local dominant plant resources of Ginkgo biloba and Zingiber officinale from Yongzhou in Hunan province, the in vitro neuroprotective and antioxidant activities of extracts from the G. biloba leaf and Z. officinale rhizome, and the correlation between these two kinds of activities, were analyzed. The in vivo effects of these two plant extracts on aged mice blood physiology and central neuron cell activity were then determined after continuous gavage with the best polarity part at different concentrations (2, 4, 8 mg/ml). The results showed that the cell survival rate and superoxide dismutase (SOD) activity of the induced injury central neurons increased, although the malondialdehyde (MDA) content decreased gradually with the extract concentrations increasing in a certain range. Different polarity parts performed differently, even though they had the same concentration, with G. biloba always performing better than the Z. officinale rhizome at the same concentration and polarity. The order of G. biloba extract from superior to inferior was ethanol, ethyl acetate, n-butanol, chloroform, water, and petroleum ether (except that the petroleum ether part performed slightly better than the water part at 0.4 and 0.5 mg/ml), while the order of Z. officinale rhizome extract from superior to inferior was ethanol, chloroform, n-butanol, ethyl acetate, water, and petroleum ether. These two plant extracts demonstrated good in vitro effect against oxygen free radicals; the scavenging rate of superoxide free radicals had a significant positive correlation with the cell survival rate. The in vivo central nerve cell activity and SOD, glutathione peroxidase (GSH-PX) activity in aged mice blood serum increased while the MDA content decreased with treatment with these two extracts (p < 0.05). There were no significant changes in the number of leukocytes, lymphocytes, red blood cells, hemoglobin content, blood urine nitrogen, uric acid, creatinine, and the enzyme activity of glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) (p > 0.05). G. biloba had a better in vivo effect than Z. officinale rhizome even though their concentration and polarity part were same. These results could provide some references for better development of these two plant extracts from Yongzhou in the field of neuroprotection.